Pro Kontra Kebijakan Pelepasan Narapidana Oleh Pemerintah di Masa Pandemi Covid-19 - Arfie Rachman Widiatama (Faculty of Law, Universitas Airlangga, 2021)
AbstractThe Indonesian Ministry of Law and Human Rights adopted a policy during the Covid-19 pandemic in the form of Permenkumham Number 10 of 2020 concerning the Terms of Providing Assimilation and Integration Rights for Prisoners and Children in Context of Preventing and Combating the Spread of Covid-19. This policy caused controversy because there were parties who refused with basis that the release of prisoners had potential to increase the crime rate, prisoners could repeat their actions. However, there are also people who support it, considering that punishment in Indonesia prioritize corporal punishment (imprisonment) and it is feared that prison is places for the transmission of the Covid-19. This paper will examine the impact of policies issued by the Ministry in relation to views in criminology which are expected to find a conclusion that can be implemented by the government regarding efforts to prevent the transmission of the Covid-19 to prisoners. Keywords: Assimilation; Integration; Prisoners; Kemenkumham; Covid-19.AbstrakKementrian Hukum dan HAM RI mengambil kebijakan di masa pandemi Covid-19 berupa Permenkumham Nomor 10 Tahun 2020 Tentang Syarat Pemberian Asimilasi Dan Hak Integrasi Bagi Narapidana Dan Anak Dalam Rangka Pencegahan Dan Penanggulangan Penyebaran Covid-19. Kebijakan ini menimbulkan kontroversi karena terdapat pihak yang menolak dengan dasar dibebaskannya narapidana berpotensi meningkatkan angka kriminalitas, narapidana ditakutkan dapat mengulang perbuatannya. Namun terdapat pula yang mendukung, mengingat hukuman di Indonesia mengutamakan pidana badan (penjara) dan ditakutkan penjara menjadi salah satu tempat penularan virus Covid-19. Tulisan ini akan mengkaji dampak kebijakan yang dikeluarkan oleh Kemenkumham dikaitkan dengan pandangan dalam kriminologi yang diharapkan dapat menemukan sebuah kesimpulan untuk dapat dijalankan pemerintah berkaitan dengan upaya pencegahan penularan virus Covid-19 terhadap narapidana.Kata Kunci: Asimilasi; Integrasi; Narapidana; Kemenkumham; Covid-19.